Preparing teachers for the use of digital technologies in their teaching practice - Vasileios Dagdilelis (Research in Social Sciences and Technology- OpenED Network, 2018)
Greece these last 15 years has developed and implemented a large-scale system for the integration of digital technologies in education and more specifically in the teaching practice.